(untitled) (Swiss Medical Weekly, 2018)
AIM OF THE STUDY Switzerland introduced the SwissDRG in 2012. The goal of this reimbursement system was to promote cost containment and efficiency in hospital care. To ensure that patients with care needs are not released prematurely because of constraints under the new hospital financing system, the Swiss law on Acute and Transitional Care (ATC) was introduced one year earlier. The objective of the present study was to investigate the impact of ATC and its effects on discharge of patients with persisting care needs after hospitalisation. METHODS Social service workers, nurses and palliative care team members at a Swiss municipal hospital were asked to complete a four-page closed-ended questionnaire about patients who require care after their hospital discharge. This included questions on discharge management, their perceptions of the appropriateness of discharge timing and details about conflicts regarding discharge. Information on length of stay, discharge location, age and sex was extracted from hospital records and matched to the information from the questionnaires. Demographic data are presented descriptively, differences between patients released to ATC and patients released elsewhere (home, nursing home, rehabilitation, etc.) were evaluated with chi-square tests. Logistic regression analyses were performed to evaluate differences between those sent to ATC and rehabilitation with age, length of stay and sex as predictors. ​ RESULTS: A total 1410 of valid questionnaires were collected, comprised of 746 female patients (52.9%) and 664 male patients (47.1%). The mean age of our patient cohort was 73.2 years (SD 15.1), and the mean hospital stay was 12.8 days (SD 9.1). After their hospital stay, 553 patients (39.2%) returned home either alone, or with the help of family members or Spitex. More than a quarter of the sample, 387 (27.4%) patients, was sent to rehabilitation. Less than a fifth, 199 (14.1%) patients, received ATC in an inpatient institution (e.g., nursing home). Compared with patients released elsewhere, significantly more problems/conflicts with regard to hospital discharge were reported for ATC patients (28.6 vs 20.6%, p = 0.01) and their relatives (12.6 vs 7.2%, p = 0.01). Women had a higher probability of being discharged to ATC (OR 1.522, p = 0.014) and a lower chance of receiving rehabilitation upon discharge (OR 0.733, p = 0.014). CONCLUSION The study identified important concerns related to receiving ATC after a hospital stay, that is, more problems/conflicts occur with patients discharged to ATC and that the introduction of ATC might particularly disadvantage female patients, who are less likely to receive rehabilitation care.